2001
DOI: 10.1046/j.1365-2427.2001.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analysis of macroinvertebrates and their food sources in a glacier stream

Abstract: 1. Food sources and trophic structure of the macroinvertebrate community along a longitudinal gradient were examined in a glacier stream of the Swiss Alps (Val Roseg). Analysis of multiple stable isotopes (δ13C and δ15N) and measurement of C : N ratios were used to differentiate between allochthonous and autochthonous organic matter. 2. Although isotopic signatures of algae varied widely among sites and dates, it was possible to discriminate between allochthonous and autochthonous food sources using a site‐spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
101
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 32 publications
13
101
1
Order By: Relevance
“…However, identification of the trophic status of some species is often problematic due to considerable feeding mode flexibility and may lead to misinterpretations. Furthermore, Zah et al (2001) claimed that aquatic invertebrates are more plastic in utilizing food resources in extreme environmental conditions (e.g. alpine and arctic streams and lakes).…”
Section: Discussionmentioning
confidence: 99%
“…However, identification of the trophic status of some species is often problematic due to considerable feeding mode flexibility and may lead to misinterpretations. Furthermore, Zah et al (2001) claimed that aquatic invertebrates are more plastic in utilizing food resources in extreme environmental conditions (e.g. alpine and arctic streams and lakes).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, seasonal changes in δ 13 C of primary producers are often rapidly reflected in the δ 13 C of invertebrates due to a high turnover rate for the assimilated carbon by the animals (Fry & Arnold 1982, Gleason 1986, Georing et al 1990, Riera & Richard 1997, Zah et al 2001. The rapidity of change and turnover of stable isotopes in animal tissues has been found even for fish and birds (Hobson & Clark 1992, Hesslein et al 1993.…”
Section: Stable Isotope Composition Of Potential Food Resources and Bmentioning
confidence: 99%
“…In the Alps, a large number of springs surface above treeline where the potential for autochthonous production is high (Zah et al, 2001;Füreder et al, 2003). Whether these ecosystems act as detritus-based systems as would be expected for springs below treeline is unknown (sensu Cross et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The grasses and herbs adjacent to alpine springs could be an important allochthonous source of organic matter and cause these systems to also rely strongly on detritus as a basal resource. In comparison, Zah et al (2001) found invertebrate herbivores in glacier streams above treeline to be reliant on autochthonous resources such as diatoms and the common gold alga Hydrurus foetidus, whereas allochthonous organic matter was an important basal resource in a nearby groundwater-fed stream (also see Füreder et al, 2003). Measures of ecosystem metabolism and stable isotope analysis of the food web would provide important information on the heterotrophic nature of alpine springs.…”
Section: Introductionmentioning
confidence: 99%